Otitis media with effusion: current treatment, new understanding of its aetiopathogenesis, and a novel therapeutic approach - Daniel, Matija (2013)
Otitis Media with Effusion (OME) is a common childhood condition leading to hearing loss, and its treatment with ventilation tubes (VTs) is one of the commonest surgical procedures. However, aetiology of OME is poorly understood, and its current treatment requires improvement as OME frequently recurs once VTs extrude.